2006
DOI: 10.14411/eje.2006.050
|View full text |Cite
|
Sign up to set email alerts
|

Responses of Sitophilus oryzae (Coleoptera: Curculionidae) and Tribolium confusum (Coleoptera: Tenebrionidae) to traps baited with pheromones and food volatiles

Abstract: Abstract. The behavioural responses of two species of stored-product beetles, Sitophilus oryzae (L.) and Tribolium confusum Jacquelin du Val, to certain stimuli were studied in laboratory choice tests. The results of these experiments indicated that, with one species present, S. oryzae and T. confusum adults were equally attracted to traps baited with the aggregation pheromone of that species and to traps baited with both pheromones. In contrast, when both species were present, neither S. oryzae nor T. confusu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
19
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 36 publications
(19 citation statements)
references
References 25 publications
0
19
0
Order By: Relevance
“…However, the efficacy of available lures for Tribolium species is uncertain in some conditions and the results may be misleading in terms of what the beetles are doing or of how dense the populations are (Trematerra et al, 2007b). The efficacy of insect traps can be enhanced substantially when a mixture of food baits and pheromones are used in traps (Athanassiou et al, 2006a). Calls have therefore been made to identify more effective lures derived from food products for enhancing insect trap catch efficiency (Cox & Collins, 2002;Collins et al, 2007).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the efficacy of available lures for Tribolium species is uncertain in some conditions and the results may be misleading in terms of what the beetles are doing or of how dense the populations are (Trematerra et al, 2007b). The efficacy of insect traps can be enhanced substantially when a mixture of food baits and pheromones are used in traps (Athanassiou et al, 2006a). Calls have therefore been made to identify more effective lures derived from food products for enhancing insect trap catch efficiency (Cox & Collins, 2002;Collins et al, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…The same is true of pest insects that invade stored grain. The adults locate the resource by responding to specific chemical cues (Chambers, 1990;Athanassiou et al, 2006a;Edde & Phillips, 2006;Nguyen et al, 2008). For example, adults of Sitophilus granarius L. respond positively to plant-produced aliphatic alcohols, aldehydes, and ketones in a pitfall olfactometer (Germinara et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, it shows resistance to insecticides (Perez-Mendoza, 1999;Fragoso et al, 2003). In studies conducted in our laboratories recently we have made significant progress in clarifying some aspects of the behavior of S. oryzae and T. confusum (Athanassiou et al, 2006). In the present work, we examined the behavioral responses of adult maize weevil to semiochemicals from several kernel categories of maize, including the interactions between kernels of different status.…”
Section: Introductionmentioning
confidence: 99%
“…Trematerra et al (2000) noted that kernels that were damaged by primary pests, especially by S. oryzae, were generally preferred by the externally feeding pests o. surinamensis, t. castaneum, and t. confusum over artificially damaged or whole kernels. Additionally, Athanassiou et al (2006) found that seeds that were damaged by S. oryzae increased the response of other S. oryzae individuals.…”
Section: Discussionmentioning
confidence: 99%